A portable, ultra-low cost, open-source, pedal-controlled microinjector for laboratory use - Victor H. Dominguez; Maxwell Frankfurter; Kevin B. Hayes; Mark L. Kahn; Martin H. Dominguez (PLoS ONE, 2026)
In vivo transduction or electroporation often requires sub-microliter volume injection of virus or recombinant DNA/RNA to a precise anatomic site. Two-hand manual manipulation of the injection needle and target tissues is dramatically faster than mechanical manipulation, but technically challenging for operators. Here, we present an all open-source, footswitch-actuated injector for nano- or microliter volumes. Our microinjector is simple, can be assembled in less than 2 hours with ordinary tools, does not require custom fabrication or soldering, and can cost less than $130 USD. This device is completely self-contained, pressure controllable, and offers both aspirate and discharge modes to facilitate multiple injections during the same procedure. Pulse-triggered discharges can reliably deliver nanoliter volumes with dispense errors of around 15%. By reducing technical and financial barriers, we anticipate this microinjector may inspire adoption of in vivo electroporation or genome editing across broader scientific communities where access may be presently limited.